A hydrogen sulfide probe activates Nrf2, inhibits cancer cell growth and induces cell apoptosis. Issue 67 (1st September 2017) - Gao, YuanDi; Ma, HanLin; Qu, GuoJing; Su, Le; Ye, Qing; Jiang, Fan; Zhao, BaoXiang; Miao, JunYing
Abstract : Application of a probe for hydrogen sulfide, HF-NBD . Abstract : It has been demonstrated that a relatively high level of endogenous hydrogen sulfide (H2 S) promotes cancer cell growth. Thus, reducing endogenous H2 S levels with a small molecule that selectively targets H2 S in cancer cells is an attractive strategy to treat cancer. In this study, we synthesized a 3-hydroxyflavone-based dual probe (HF-NBD ) targeting H2 S with favourable photostability, and found that it could also activate the nuclear factor erythroid-2-related factor 2 (Nrf2) and upregulate heme oxygenase-1 (HO-1) expression.HF-NBD inhibited the growth of A549 lung cancer cells, U87 malignant glioma cells and HeLa cervical cancer cells, and induced apoptosis in HeLa cells. Herein we provideHF-NBD, a novel Nrf2 activator that promotes HO-1 expression downstream of Nrf2. The data suggested thatHF-NBD might be a potential lead compound for the development of new anti-cancer drugs.